Pembangunan kaedah mengfenotip dan penentukuran apolipoprotein E - Rashid, Faridah Abdul (1999)
Apolipoprotein E phenotyping studies were performed on 17 samples from blood donors and selected subjects. One unit of plasma of 150- 270 ml were collected from each subject. VLDL (very law density lipoproteins) were separated from plasma by ultracentrifugation. VLOL obtained (10% plasma volume) were delipidated to remove lipid components and only proteins remained. Protein electrophoresis by isoelectric focussing technique performed in a pH gradient of 4.0-6.5 resulted in 10 protein bands after staining with Coammassie Brilliant Blue. Bands were road by eye without scanning. The apolipoprotetn E phenotyping results obtained were: E4/3(59%), E3/2(12%), E3/3(18%), E2/2(12%). Two apolipaprotein E phenotypes not seen were E4/4 and E4/2. Two E413 cases were deficient in apolipoprotein A-l: one was ambiguous as to whether it was E4/3 or E4/2. One E3l2 case was deficient in apolipoprotein E, A-1, dan C-11. Three cases of E3/3 were deficient in apolipoprctein A-1 and one of them was also deficient for both A-1 and C-ll. Apolipoprotein E levels was low for one case of E3/2 one case of E3/3 and one case of E2/2. Continued research in this field has been expanded to include apolipoprotein E genotyping studies and to further accommodate other plasma proteins of clinical interest.